2020
DOI: 10.1186/s13024-020-00407-2
|View full text |Cite
|
Sign up to set email alerts
|

Higher CSF sTREM2 attenuates ApoE4-related risk for cognitive decline and neurodegeneration

Abstract: Background The Apolipoprotein E ε4 allele (i.e. ApoE4) is the strongest genetic risk factor for sporadic Alzheimer’s disease (AD). TREM2 (i.e. Triggering receptor expressed on myeloid cells 2) is a microglial transmembrane protein brain that plays a central role in microglia activation in response to AD brain pathologies. Whether higher TREM2-related microglia activity modulates the risk to develop clinical AD is an open question. Thus, the aim of the current study was to assess whether higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 57 publications
1
38
0
Order By: Relevance
“…However, these authors did show that WT sTREM2 bound strongly to amyloid plaques ( 34 ), consistent with our results. Our studies provide a potential explanation of the clinical observation of slower rates of cognitive and clinical decline in patients with MCI or AD who have higher levels of sTREM2 in the CSF ( 20 , 21 ) and slower rates of amyloid deposition in healthy controls and MCI patients with higher sTREM2 levels in CSF ( 22 ). They also provide a potential explanation for the beneficial effects of infusing or expressing sTREM2 into the brain of mouse models of AD ( 16 ).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, these authors did show that WT sTREM2 bound strongly to amyloid plaques ( 34 ), consistent with our results. Our studies provide a potential explanation of the clinical observation of slower rates of cognitive and clinical decline in patients with MCI or AD who have higher levels of sTREM2 in the CSF ( 20 , 21 ) and slower rates of amyloid deposition in healthy controls and MCI patients with higher sTREM2 levels in CSF ( 22 ). They also provide a potential explanation for the beneficial effects of infusing or expressing sTREM2 into the brain of mouse models of AD ( 16 ).…”
Section: Discussionmentioning
confidence: 78%
“…However, the CSF Aβ levels rise in the early symptomatic stages of AD and then decline again at later stages of AD (11,12). Fifth, mild cognitive impairment (MCI) and AD patients with higher sTREM2 levels in CSF have slower brain atrophy, cognitive decline, and clinical decline (20,21), consistent with sTREM2 inhibiting AD progression. Sixth, healthy controls and MCI patients with higher sTREM2 levels in CSF have slower progression of amyloid and tau deposition (22), consistent with sTREM2 inhibiting Aβ aggregation and subsequent tau pathology.…”
mentioning
confidence: 99%
“…Based on our results, serum sTREM2 levels in the older adults might not be considered as a biomarker for predicting a decline in future cognitive functions or brain volume. Recently, it has been suggested that higher CSF sTREM2 attenuates risk for cognitive decline and TREM2 may be protective against the development of AD ( Franzmeier et al, 2020 ). Although measuring sTREM2 level in peripheral blood is less invasive and relatively easily, it might be necessary to analyze the relationship between the CSF sTREM2 levels and brain volume.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies are broadly congruent with previous research showing that knockout of TREM2 expression in APP mice, resulted in accelerated amyloid plaque seeding 17 , with increased protofibrillar halos and hotspots around these plaques 3,16,18 . Our studies provide a potential explanation of the clinical observation of slower rates of cognitive and clinical decline in patients with MCI or AD who have higher levels of sTREM2 in the CSF 20,21 , and slower rates of amyloid deposition in healthy controls and MCI patients with higher sTREM2 levels in CSF 22 . They also provide a potential explanation for the beneficial effects of infusing or expressing sTREM2 into the brain of mouse models of AD 16 .…”
Section: Discussionmentioning
confidence: 69%